Display Formula
$Rr=2R2J12(\rho pr*){\u2211\Omega \kappa r\kappa \Omega ([mrm\Omega +mr2]S\u22121(pr,p\Omega ,pr*)+[GnrGn\Omega +Gnr2]R2S1(pr,p\Omega ,pr*))\Vert mr+m\Omega =mr*nr+n\Omega =nr*\Vert}|prmrnr$(14)
Display Formula$\phi r=2jR2J12(\rho pr*){\u2211\Omega \kappa \phi \kappa \Omega (m\Omega +m\phi )[S\u22121(p\phi ,p\Omega ,pr*)+\rho p\phi To(p\phi ,p\Omega ,pr*)]\Vert m\phi +m\Omega =mr*n\phi +n\Omega =nr*\Vert}|p\phi m\phi n\phi $(15)
Display Formula$Zr=\u22122jRJ12(\rho pr*){\u2211\Omega \kappa z\kappa \Omega [(\rho pz)[Gn\Omega +Gnz]T1(pz,p\Omega ,pr*)]\Vert mz+m\Omega =mr*nz+n\Omega =nr*\Vert}|pzmznz$(16)
Display Formula$R\phi =\u22122jR2J12(\rho p\phi *){\u2211\Omega \kappa r\kappa \Omega mr[S\u22121(pr,p\Omega ,p\phi *)+\rho prTo(pr,p\Omega ,p\phi *)+\rho p\Omega Uo(pr,p\Omega ,p\phi *)]\Vert mr+m\Omega =m\phi *nr+n\Omega =n\phi *\Vert}|prmrnr$(17)
Display Formula$\phi \phi =2J12(\rho p\phi *){\u2211\Omega \kappa \phi \kappa \Omega [(Gn\phi Gn\Omega +Gn\phi 2+\rho p\phi 2R2)S1(p\phi ,p\Omega ,p\phi *)+1R2S\u22121(p\phi ,p\Omega ,p\phi *)+(\rho p\Omega R2)Uo(p\phi ,p\Omega ,p\phi *)\u2212(\rho p\phi \rho p\Omega R2V1(p\phi ,p\Omega ,p\phi *))]\Vert m\phi +m\Omega =m\phi *n\phi +n\Omega =n\phi *\Vert}|p\phi m\phi n\phi $(18)
Display Formula$Z\phi =\u22122RJ12(\rho p\phi *){\u2211\Omega \kappa z\kappa \Omega mz([Gn\Omega +Gnz]So(p\phi ,p\Omega ,p\phi *))\Vert mz+m\Omega =m\phi *nz+n\Omega =n\phi *\Vert}|pzmznz$(19)
Display Formula$Rz=2jRJ12(\rho pz*){\u2211\Omega \kappa r\kappa \Omega [GnrSo(pr,p\Omega ,pz*)\u2212Gnr\rho prT1(pr,p\Omega ,pz*)\u2212Gnr\rho p\Omega U1(pr,p\Omega ,pz*)]\Vert mr+m\Omega =mz*nr+n\Omega =nz*\Vert}|prmrnr$(20)
Display Formula$\phi z=\u22122RJ12(\rho pz*){\u2211\Omega \kappa \phi \kappa \Omega Gn\phi ([m\Omega +m\phi ]So(p\phi ,p\Omega ,pz*))\Vert m\phi +m\Omega =mz*n\phi +n\Omega =nz*\Vert}|p\phi m\phi n\phi $(21)
Display Formula$Zz=2J12(\rho pz*){\u2211\Omega \kappa z\kappa \Omega [(\rho pzR)2S1(pz,p\Omega ,pz*)+(mzm\Omega +mz2R2)S\u22121(pz,p\Omega ,pz*)\u2212(\rho pz\rho p\Omega R2V1(pz,p\Omega ,pz*))]\Vert mz+m\Omega =mz*nz+n\Omega =nz*\Vert}|pzmznz$(22)